1995
DOI: 10.1128/jvi.69.7.4323-4330.1995
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of the c-fos gene by YY1 is mediated by a direct interaction with ATF/CREB

Abstract: Transcriptional activation of the mouse c-fos gene by the adenovirus 243-amino-acid E1A protein requires a binding site for transcription factor YY1 located at ؊54 of the c-fos promoter. YY1 normally represses transcription of c-fos, and this repression depends on the presence of a cyclic AMP (cAMP) response element located immediately upstream of the ؊54 YY1 DNA-binding site. This finding suggested that the mechanism of transcriptional repression by YY1 might involve a direct interaction with members of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…Further analyses are needed to elucidate the mechanism of action of YY1 in relation to brain-specific region ADORA2A expression. For instance, it needs to be examined whether it forms a repression complex with histone deacetylase (HDAC)1/2 (Thomas and Seto 1999), or whether it interacts with cAMPresponse element binding protein, interfering with its positive role above cerebellar ADORA2A expression (Zhou et al 1995;Chiang et al 2005). Interestingly, the formation of YY1/ZBP-89 complex, reducing the ability of ZBP-89 to activate gene expression, has been described (Boopathi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses are needed to elucidate the mechanism of action of YY1 in relation to brain-specific region ADORA2A expression. For instance, it needs to be examined whether it forms a repression complex with histone deacetylase (HDAC)1/2 (Thomas and Seto 1999), or whether it interacts with cAMPresponse element binding protein, interfering with its positive role above cerebellar ADORA2A expression (Zhou et al 1995;Chiang et al 2005). Interestingly, the formation of YY1/ZBP-89 complex, reducing the ability of ZBP-89 to activate gene expression, has been described (Boopathi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A number of proteins are known to physically interact with YY1, some within the zinc finger region. These YY1 interacting proteins include TBP, CBP, p300, TFIIB, c-myc, Sp1, ATF2, CREB, AP1, TAFII 55 , and E1A [Usheva and Shenk, 1994, Chiang and Roeder, 1994Seto et al, 1993;Zhou et al, 1995;O'Connor et al, 1996;Shrivastava et al, 1993;Yang et al, 1996;Austen et al, 1997;Shi et al, 1991]. YY1 sequences 333-371 could potentially inhibit enhancer activity by physically interacting with one or more of these proteins thereby disrupting transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Protein interactions with YY1 can also lead to loss of activated transcription. For instance, interaction of YY1 with transcriptional activators such as ATF/ CREB and AP1 can lead to loss of activated transcription [Zhou et al, 1995;O'Connor et al, 1996]. In addition, YY1 can repress human papilloma virus type 16 transcription by quenching AP1 activity [O'Connor et al, 1996].…”
mentioning
confidence: 99%
“…Looking for a mammalian functional equivalent of the unknown VP1-binding transcription factor of yeast, we had discovered the direct interaction of VP1 with the pleiotropic transcription regulator, YY1 [31]. Zhou et al [32] have suggested that the YY1 -ATF/CREB complex serves as a target for the adenovirus E1A 243 protein. Members of the mammalian ATF/CREB family of transcription factors are associated with regulation by cAMP.…”
Section: Inhibition Of Yeast Cell Growth By Vp1 Ala and Vp1 Wt In A Cmentioning
confidence: 99%